Cytokine-Based Generation of CD49a+Eomes−/+ Natural Killer Cell Subsets - Ni, Xiang; Fu, Binqing; Zhang, Jinghe; Sun, Rui; Tian, Zhigang; Wei, Haiming (Frontiers in Immunology, 2018)
Recent studies have identified CD49a+Eomes− and CD49a+Eomes+ subsets of tissue-resident NK (trNK) cells in different organs of the mouse. However, the characteristics of CD49a+Eomes−/+ NK cell development and the regulation of Eomes expression in NK cells remain unclear. Here, we established an in vitro cytokine-based feeder-free system in which bone marrow progenitor cells differentiate into CD49a+ NK cells. IL-15 was identified as being the key cytokine in this system that supported the development and maintenance of CD49a+ NK cells. The CD49a+ NK cells generated were Eomes−CD49b− and shared the same phenotype as hepatic trNK cells. IL-4 induced the expression of Eomes in generated NK cells and converted them into CD49a+Eomes+ cells, which were phenotypically and functionally similar to uterine trNK cells. Moreover, the IL-4/STAT6 axis was identified as being important in the generation of CD49a+Eomes+ induced NK cells. Collectively, these studies describe an approach to generate CD49a+Eomes−/+ subsets of NK cells and demonstrate important roles for IL-15 and IL-4 in the differentiation of these cells. These findings have potential for developmental research underlying the generation of different subsets of NK cells and the application of adoptive NK cell transfer therapies.